Including women in public affairs departments: Diversity is not enough - Edwards, Lauren Hamilton; Holmes, Maja Husar; Sowa, Jessica E. (Journal of public affairs education : J-PAE., 2019)
The representation of women in faculty roles within universities broadly and within public affairs departments specifically has been evolving over the past three decades. However, diversifying gender representation in public affairs faculties is not sufficient. Barriers for success remain for women in public affairs departments. Bias exists in hiring and promotion decisions, imbalanced expectations of institutional norms and expectations persist, and fault lines emerge through the diversification of departments. Inclusion is the necessary next step to make representation more meaningful implementation of diversity. The article provides suggestions on how public affairs departments can promote more inclusive climates to elicit the positive effects of gender diversity and alleviate the negative consequences of more diverse faculties.